Risk factors and clinical characteristics associated with a ruptured ectopic pregnancy: A 19-year retrospective observational study. Issue 24 (17th June 2022) - Li, Pei-Chen; Lin, Wen-Yu; Ding, Dah-Ching
Abstract : Abstract: Ectopic pregnancy is the most common cause of maternal mortality in the first trimester of pregnancy. The aim of this study was to find risk factors and clinical characteristics associated with ruptured ectopic pregnancies at a medical center in eastern Taiwan in a 19-year period. This was a retrospective observational study that included patients diagnosed with ectopic pregnancy between August 1999 and December 2018. Data about the demographic variables, initial presentation, pre-treatment beta-human chorionic gonadotropin levels, treatment routes (laparoscopy or laparotomy), surgical methods (salpingostomy or salpingectomy), operation time, blood loss amount, the status of ectopic pregnancy (ruptured or unruptured), the requirement for transfusion, and duration of hospital stay were collected. The categorical and continuous variables were analyzed using the correlation coefficients. This study included 225 women who were diagnosed as having an ectopic pregnancy. There were 49 and 176 women with unruptured and ruptured ectopic pregnancies, respectively. The beta-human chorionic gonadotropin levels, history of previous ectopic pregnancy, pelvic inflammatory disease, tubal surgery, abdominal history, and vaginal bleeding were not significantly different between the 2 groups. The ratio of women with abdominal pain was significantly higher in the ruptured ectopic pregnancy group than in the unruptured group (89.1% vs. 63.8%, respectively, P < .001). Preoperative hemoglobin was lower in the ruptured group compared with the unruptured group ( P < .001). Blood loss, postoperative hemoglobin, and blood transfusion were significantly higher in the ruptured group than in the unruptured group ( P = .000 and P = .001 for blood loss and blood transfusion, respectively). Multiple logistic regression analysis revealed that abdominal pain and blood loss were associated with ruptured tubal pregnancies (adjusted odds ratio [95% confidence intervals]: 3.42 1.40, 8.40; 1.01 1.005, 1.014, respectively). In conclusion, early pregnancy with abdominal pain, more parity, and lower preoperative hemoglobin should be aware of the possibility of ruptured ectopic pregnancy. More blood loss, transfusion and lower postoperative hemoglobin were also noted with ruptured ectopic pregnancy.